Pueblo de humanos: metáforas corporales y diferenciación social indígena en Bolivia - Salazar, Cecilia (Pontificia Universidad Católica del Perú. Fondo Editorial, 2006)
The social differentiation of indigenous groups, in the Andean region of Bolivia, takes place against the backdrop of the notion of "desanclaje" (disanchoring). According to this, the transit from an agrarian society to an industrial society generates in individuals a sort of "estrangement" from their local and traditional relationships of presence. This relationships are then structures at the space time intervals of modernity and capitalism through the notion of a state-nation. Education plays a key role in this process that is made visible through one of the main consequences that the differenced and unequal integration of indigenous groups to the state order entails, the social division of labor generating a separation between manual workers and intellectuals. . All these aspects are analiyzed on the basis of body metaphors that refer to the complex administration of signs and meanings under the periods of colonization and capitalism in the Andean region of Bolivia.

La diferenciación social de los indígenas, en la región andina de Bolivia, tiene como telón de fondo la noción de «desanclaje». Según esta, el tránsito de la sociedad agraria hacia la sociedad industrial produce una forma de «extrañamiento» del ser humano respecto de sus relaciones locales y tradicionales de presencia, para estructurarlas luego en intervalos espaciales y temporales de la modernidad y el capitalismo, en su forma estatal-nacional. En este proceso, la educación desempeña un papel fundamental que el artículo hace visible a partir de una de las consecuencias centrales de la integración diferenciada y desigual de los indígenas al orden estatal, ello a través de la división social del trabajo que deviene en sujetos intelectuales y manuales. Todos estos aspectos son tratados desde metáforas corporales que aluden a la compleja administración de signos y significantes bajo los formatos comprensivos de la colonización y el capitalismo en los Andes de Bolivia.
Village of humans: body metaphors and indigenous social differentiation in Bolivia
Keywords: Diferenciación social; Etnicidad; Identidad nacional; Nacionalismo; https://purl.org/pe-repo/ocde/ford#5.04.03